Bifurcations and instabilities in rotating, two-layer fluids: II. beta-plane - Lovegrove, A; Moroz, I; Read, P (2002)
In this paper, we show that the behavior of weakly nonlinear waves in a 2-layer model of baroclinic instability on a P-plane with varying viscosity is determined by a single degenerate codimension three bifurcation. In the process, we show how previous studies, using the method of multiple scales to derive evolution equations for the slowly varying amplitude of the growing wave, arise as special limits of the general evolution description.